#### If a = c^{z}, b = a^{x} and c = b^{y}, prove that xyz = 1.

**Solution:**

It is given that

a = c^{z}, b = a^{x} and c = b^{y}

We can write it as

a = (b^{y})^{z} where c = b^{y}

So we get

a = b^{yz}

Here

a = (a^{x})^{yz}

a^{1} = a^{xyz}

By comparing both

xyz = 1

Therefore, it is proved.

**More Solutions:**

- Simplify the following: (i) (81/16)-3/4.
- Simplify the following : (i) (2a-3b2)3
- Simplify the following: (i) 3a/b-1 + 2b/a-1
- Simplify the following: (i) (8/125)-1/3
- Simplify the following : (i) (-1/27)-2/3
- Simplify the following Indices:
- Evaluate the following indices:
- Simplify the following:(i) (3×2)-3 × (x9)2/3
- Simplify the following: (i) (32)0 + 3-4 × 36 + (1/3)-2